Treatment of Skin Hyperpigmentation using Q-Switched (1064nm and 532nm) Nd:YAG Laser - Saadi, Ali AL-; Mahmood, Ali S. (Iraqi Journal of Laser, 2019)
Hyperpigmentation is the increase in the natural color of the skin. The purpose of this study is to evaluate the efficacy and safety of Q-Switched Nd:YAG (1064 & 532 nm) Laser in treatment of skin hyper pigmentation. This study was done in the research clinic of Institute of laser for postgraduate Studies/University of Baghdad from October 2008 to the end of January 2009. After clinical assessment of skin hyperpigmentation color, twenty six patients were divided according to their lesions. Eight Patients with freckles, seven patients with melasma, four patients with tattoo. Cases with tattoo, were subdivided into amateur tattoos two, professional tattoos one, and one traumatic tattoo. Four Patients with post inflammatory hyperpigmentation, one patient with gazzal eye, one patient with spilus nevus, one patient with becker’s nevus. The time of treatment session was from 5-20 minutes according to the size of lesion at 3-4 week interval. The distributions of lesions were on different part of body, face, hand, forearm, and back. Twenty two patients completed the study; four patients defaulted from the study for unknown reasons. Conclusion: The use of Q-Switched lasers offers a low risk, effective therapy with minimal side effects because they offer bloodless, low risk, effective treatment, Q-Switched Nd:YAG lasers have replaced other methods and are now considered standard treatment. The Q-Switched Nd:YAG laser have great advantages in removing hyperpigmentation, its longer wavelength (1064nm) would increase dermal penetration and decrease melanin absorption so that it’s used in skin type (III,IV,V,VI) without the risk of depigmentation or hypopigmentation.